Diseño de intersección vial urbana en la entrada principal del ingreso de la Utmach - Belduma Lojano, Juan Gabriel (My University, 2023)
Over the years, the population grows at the national level, so problems arise, be they social, environmental, economic, etc. The provincial capital is growing rapidly and has this state highway that connects with different cantons, which is why a vehicular conflict is generated, causing movement difficulties, and the solutions are a request for civil engineering technicians. Therefore, roundabouts are mostly positive points for traffic, since they act as a mitigator for vehicular conflicts and road intersections. Therefore, in this case it is based on the study of the intersection of Panamericana avenue and the entrance road to Utmach, being a main road with greater growth at the city level. Thus, in the project, a roundabout was created between Panamericana avenue and the entrance road to the University of Machala, located in the town of Machala, in the El Oro area, for which photogrammetry was used to capture topographic information, for later begin to enter the topographic information obtained and use Civil 3D (Vehicle Tracking) software that allows us to design the roundabout and for this we have taken the FHWA (Federal Highway Administration) as referential regulations.
Con el paso de los años, la población crece a nivel nacional, por lo que surgen problemas, ya sean sociales, ambientales, económicos, etc. La capital provincial crece de manera acelerada y cuenta con esta vía estatal que conecta con distintos cantones por lo que se genera un conflicto vehicular ocasionando dificultades de movimiento, y las soluciones son una solicitud para los técnicos de la ingeniería civil. Por lo tanto, las rotondas son en su mayoría son puntos positivos para el tránsito, pues actúan como un mitigador a los conflictos vehiculares e intersecciones viales. Por lo que en este caso se basa al estudio de la intersección de la avenida Panamericana y la vía de ingreso a la Utmach siendo una vía principal con mayor crecimiento a nivel de la ciudad. Así, en el proyecto, se creó una rotonda entre la avenida Panamericana y vía de ingreso a la Universidad de Machala, ubicada en la localidad de Machala, en la zona de El Oro, para ello se usó fotogrametría para capturar información topográfica, para posteriormente comenzar a ingresar la información topográfica obtenida y usar Civil 3D (Vehicle Tracking)software que nos permite el diseño de la rotonda y para ello hemos tomado como normativa referencial a la FHWA (Federal Highway Administration).
Keywords: INTERSECCION; CIVIL 3D; ROTONDA; FOTOGRAMETRIA